Heat shock factor binding protein BrHSBP1 regulates seed and pod development in Brassica rapa - Muthusamy, Muthusamy; Son, Seungmin; Park, Sang Ryeol; Lee, Soo In (Frontiers in Plant Science, 2023)
Plant heat shock factor binding proteins (HSBPs) are well known for their implication in the negative regulation of heat stress response (HSR) pathways. Herein, we report on the hitherto unknown functions of HSBP1 in Brassica rapa (BrHSBP1). BrHBSP1 was found to be predominant in flower buds and young leaves, while its segmental duplicate, BrHSBP1-like, was abundant in green siliques. Exposure to abiotic stress conditions, such as heat, drought, cold, and H2O2, and to phytohormones was found to differentially regulate BrHSBP1. The activity of BrHSBP1-GFP fusion proteins revealed their cellular localization in nuclei and cytosols. Transgenic overexpression of BrHSBP1 (BrHSBP1OX) improved pod and seed sizes, while CRISPR-Cas BrHSBP1 knock-out mutants (Brhsbp1_KO) were associated with aborted seed and pod development. The transcriptomic signatures of BrHSBP1OX and Brhsbp1_KO lines revealed that 360 and 2381 genes, respectively, were differentially expressed (Log2FC≥2, padj<0.05) expressed relative to control lines. In particular, developmental processes, including plant reproductive structure development (RSD)-related genes, were relatively downregulated in Brhsbp1_KO. Furthermore, yeast two-hybrid assays confirmed that BrHSBP1 can physically bind to RSD and other genes. Taking the findings together, it is clear that BrHSBP1 is involved in seed development via the modulation of RSD genes. Our findings represent the addition of a new regulatory player in seed and pod development in B. rapa.